PENINGKATKAN MINAT DAN HASIL BELAJAR MATERI TEKANAN HIDROSTATIS DENGAN MEDIA KOMIK PIXTOON - Atikah Humairoh; Stepanus Sahala Sitompul; Hamdani Hamdani (Universitas Tanjungpura, 2021)
AbstractThis study aims to identify comic-based learning media in an effort to increase students interest and learning outcomes in hydrostatic pressure material. This study uses the use of a technology-based application called Pixtoon that researchers use to develop the creation of science learning comilk on hydrostatic pressure material in class VIII A1 SMP Negeri 4 Selakau. In the learning process, researchers applied a cooperative learning model with nht (numbered head together) type. Based on the analysis of data, it concluded that the tests developed are worth using to improve the learning outcomes of learners, namely: 1) have a higher validity than the validity of the table, 2) The average results of the student questionnaire before using comic learning media is 1.84. And the average result after using comic learning media is 3.40, so it can be stated that the interest of learners in comic-based learning can increase the learning interest of learners.. 3) pretest value reached 21.18 while postest reached 72.94 so that the difference score was 51.76, 4) the result of the response of students to comic-based learning media is 3.09 with the category